Manipulating theophany : light and ritual in north Adriatic architecture (ca. 400-ca. 800) - Ivanovici, Vladimir (De Gruyter, 2016)
Using light as fil rouge reuniting theology and ritual with the architecture, decoration, and iconography of cultic spaces, the present study argues that the mise-en-scène of fifth-century baptism and sixth-century episcopal liturgy was meant to reproduce the luminous atmosphere of heaven. Analysing the material culture of the two sacraments against common ritual expectations and Christian theology, we evince the mannerin which the luminous effect was reached through a combination of constructive techniques and perceptual manipulation. One nocturnal and one diurnal, the two ceremonials represented different scenarios, testifying to the capacity of church builders and willingness of Late Antique bishops to stage the ritual experience in order to offer God to the senses.
Keywords: Paulinus, -- of Nola, Saint, -- approximately 353-431.; Paulinus, -- of Nola, Saint, -- approximately 353-431; Licht, ...; Wat, Aleksander, -- 1900-1967.; Watowa, Ola, -- 1903-1991 -- Entretiens.; Worship -- History -- Early church, ca. 30-600.; Liturgies, Early Christian.; Baptism -- History -- Early church, ca. 30-600.; Liturgy and architecture.; Light in architecture.; Architecture -- Italy -- Ravenna.; Light -- Religious aspects -- Christianity.; Ravenna (Italy) -- Church history.; Cultes -- Histoire -- ca 30-600 (Église primitive); Liturgie chrétienne primitive.; Baptême -- Histoire -- ca 30-600 (Église primitive); Liturgie et architecture.; Lumière en architecture.; Architecture -- Italie -- Ravenne.; RELIGION -- Christian Rituals & Practice -- Worship & Liturgy.; RELIGION -- Institutions & Organizations.; Architecture; Baptism -- Early church; Light in architecture; Light -- Religious aspects -- Christianity; Liturgies, Early Christian; Liturgy and architecture; Worship -- Early church; Italy -- Ravenna; Frühchristentum; Kirchenbau; Liturgie; Symbolik; Venetien; Art -- Aspect social -- Hongrie -- 1870-1914 -- Catalogues d'exposition.; Art -- Hongrie -- 1870-1914 -- Catalogues d'exposition.; Marché du travail -- France -- Franche-Comté (France) -- Statistiques.; Migrations alternantes -- France -- Franche-Comté (France); 30-600; Church history; History